A phase I study of panobinostat and ruxolitinib in patients with primary myelofibrosis (PMF) and post-polycythemia vera/essential thrombocythemia myelofibrosis (post-PV/ET MF). (January 2020) - Mascarenhas, J.; Marcellino, B.K.; Lu, M.; Kremyanskaya, M.; Fabris, F.; Sandy, L.; Mehrotra, M.; Houldsworth, J.; Najfeld, V.; El Jamal, S.; Petersen, B.; Moshier, E.; et al.
Highlights: Combination of panobinostat and ruxolitinib in MF patients is safe and well tolerated. Clinical improvement was seen in 40 % of patients treated with this combination therapy. First pre-clinical driven, JAK inhibitor-based combination therapy approach in MF. Abstract: Ruxolitinib, a selective JAK1/JAK2 inhibitor, is the current first line therapy for myelofibrosis (MF), which reduces symptomatology and splenomegaly, but does not clearly modify disease course. Panobinostat, a histone deacetylase inhibitor, was shown to be safe and tolerable in phase I and II trials and demonstrated clinical activity in approximately a third of treated patients. Combination therapy of ruxolitinib and panobinostat showed synergistic activity in a preclinical MF model, which prompted clinical evaluation of this combination in both ruxolitinib naïve and treated MF patients. Herein, we report the results of an investigator-initiated, dose escalation, phase I trial of ruxolitinib and panobinostat in 15 patients with primary MF and post-polycythemia vera/essential thrombocythemia MF. This combination treatment proved to be safe and tolerable without dose limiting thrombocytopenia and a maximum tolerated dose of both agents in combination was not determined. The majority of patients maintained stable disease with this combination treatment and 40 % attained a clinical improvement (spleen n = 5, anemia n = 1) by modified IWG-MRT at the end of 6 cycles. This is one of the first attempts of rationally designed, JAK inhibitor-based, combination therapy studies and exemplifies the feasibility of such an approach in patients with advanced MF.